Environmental risk factors associated with community diarrheal disease in Ethiopia - LaPolt, D.; Smith, S.; Gazu, Lina; Alonso, Silvia; Teshale, A.M.; Azmeraye, B.M.; Ayana, G.M.; Angaw, D.A.; Degefaw, D.; Garsow, A.V.; Beczkiewicz, A.; Yimer, G.; et al. (BioMed Central, 2025)
Background: Diarrhea is a major contributor to mortality in sub-Saharan Africa, where access to improved sanitation and clean water is limited. Identifying factors associated with diarrhea across geographical regions and age groups can inform resource allocation toward water infrastructure, healthcare, and disease mitigation. The objective of this study was to identify environmental risk factors associated with diarrhea in the general population across multiple communities in Ethiopia.